Perancangan Aplikasi Point of Sale (POS) pada Karya Maju Jaya - Martono Martono; Zulfi Karman (Jurnal Processor, 2022)
Karya maju jaya is one of the shops that engaged in the provision of services and goods in the form of workshops. Currently at karya maju Jaya, the process of managing transactions and financial reports still uses paper media as a means of storing data, causing many weaknesses in terms of security, effectiveness from the aspect of time, higher costs to the high possibility of errors in processing and processing information. Therefore, the author decided to conduct a research that the author gave the title point of sale (POS) application design on the work of karya maju jaya with the aim of answering all the problems above. The point of sale (POS) application in this study will be described using use case diagrams and class diagrams modeling. The final product of the research that the author did in this research is a point of sale (POS) application that allows application users to process product data, manage transaction data, manage reports, manage invoices, manage profiles, change passwords, login and logout.